1998
DOI: 10.1246/cl.1998.1093
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Stereochemistry and CD Spectra of Resolved Enantiomers of the Colored Form of a Photochromic Dithienylethene

Abstract: The colored form of photochromic 1,2-bis(5-hydroxymethyl-2-methyl-3-thienyl)hexafluorocyclopentene was resolved into enantiomers by HPLC. The absolute stereochemistry of an enantiomer was determined on its bis(4-chlorobenzoate). The CD spectra and optical rotation of the resolved colored form were measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…This photoinduced change is not limited to the color or absorption spectra, as the change occurs between two different molecules with different physical and chemical properties. When a photochromic compound is chiral and non‐racemic,2 its chiroptical properties such as circular dichroism spectra3, 4 and optical rotation57 also change reversibly. These chiral and chiroptical differences can be used to: 1) detect the state of the system without inducing any property change,57 2) induce and control the alignment of a chiral nematic liquid crystal in a sensitive manner,810 or 3) make a chiral complex11 that may work as a chiral catalyst 12…”
Section: Spectroscopic and Photoreaction Data For 1–3 In Ethyl Acetatementioning
confidence: 99%
“…This photoinduced change is not limited to the color or absorption spectra, as the change occurs between two different molecules with different physical and chemical properties. When a photochromic compound is chiral and non‐racemic,2 its chiroptical properties such as circular dichroism spectra3, 4 and optical rotation57 also change reversibly. These chiral and chiroptical differences can be used to: 1) detect the state of the system without inducing any property change,57 2) induce and control the alignment of a chiral nematic liquid crystal in a sensitive manner,810 or 3) make a chiral complex11 that may work as a chiral catalyst 12…”
Section: Spectroscopic and Photoreaction Data For 1–3 In Ethyl Acetatementioning
confidence: 99%
“…This photoinduced change is not limited to the color or absorption spectra, as the change occurs between two different molecules with different physical and chemical properties. When a photochromic compound is chiral and non-racemic, [2] its chiroptical properties such as circular dichroism spectra [3,4] and optical rotation [5][6][7] also change reversibly. These chiral and chiroptical differences can be used to: 1) detect the state of the system without inducing any property change, [5][6][7] 2) induce and control the alignment of a chiral nematic liquid crystal in a sensitive manner, [8][9][10] or 3) make a chiral complex [11] that may work as a chiral catalyst.…”
Section: Yasushi Yokoyama* Tatsuya Shiozawa Yutaka Tani and Takashmentioning
confidence: 99%
“…For 2 O, the spectrum showed a negative Cotton effect in the visible region, indicating that the major enantiomer of 2 C has an S,S configuration, as already mentioned. [9] On the other hand, 1 O showed a slight positive Cotton effect in the visible region. Matsuda et al have reported that the sign of rotatory strength for an R,R enantiomer of the C-form available by the photoirradiation of 1,2-bis(5-substituted-2-me-A C H T U N G T R E N N U N G thylthienyl)hexafluorocyclopentenes is positive when the pconjugating substituent is no larger than a vinyl group, whereas it is negative when the conjugating group is larger than a vinyl group, such as in the case of phenyl or formyl groups.…”
mentioning
confidence: 93%
“…Fortunately, we had previously determined the absolute stereochemistry of optically resolved enantiomers of 2 C by X-ray crystallographic analysis [9] so that the slower moving major enantiomer of 2 C was identified as the S,S configuration. They exhibited photocyclization in the presence of HSA with 313 nm light.…”
mentioning
confidence: 99%
See 1 more Smart Citation